Maternal hypertriglyceridemia: A link between maternal overweight‐obesity and macrosomia in gestational diabetes. (23rd June 2014) - Olmos, Pablo R.; Rigotti, Attilio; Busso, Dolores; Berkowitz, Loni; Santos, José L.; Borzone, Gisella R.; Poblete, José A.; Vera, Claudio; Belmar, Cristián; Goldenberg, Denisse; Samith, Bárbara; Acosta, Ana M.; et al.
<x xml:space="preserve">Abstract</x> Objective Infants born from overweight and obese mothers with glucose‐controlled gestational diabetes (GDM) tend to be large‐for‐gestational age (LGA). It is hypothesized that this is due to an excessive rise in maternal triglyceride levels. Methods Two‐hundred and seventy nine singleton GDM pregnancies were divided into three groups according to prepregnancy BMI: normal weight (BMI = 20–24.9; n = 128), overweight (BMI = 25–29.9; n = 105), and obese (BMI ≥ 30; n = 46). Individual z‐scores (ZS) of maternal triglycerides and of newborn weight (NWZS) were calculated as deviations from published 50th percentiles. Mean z‐scores (MZS) were the average of triglyceride ZSs. MZS of triglycerides, HbA1c and NWZS were compared. Variables are expressed as mean ± SD. Results In the three groups respectively: LGA (%) = 10.1%, 19.0% and 30.4% (P = 0.015). Birth weight (g) = 3274.2 ± 501.3, 3342.4 ± 620.2 and 3366.3±644.7 (RSPEARMAN = 0.111, P = 0.027). HbA1c (%) = 5.2 ± 0.39, 5.3 ± 0.50 and 5.4 ± 0.47 (P = NS). Triglyceride MZS = 1.20 ± 1.13, 1.52 ± 1.37 and 1.62 ± 1.42 (RSPEARMAN= 0.116, P = 0.024). Correlations between triglyceride MZS and NWZS were, respectively: r = 0.12 (P = NS), r = 0.42 (P <0.001), and r = 0.47 (P < 0.001). Conclusions In overweight and obese GDM mothers, maternal triglycerides are partially responsible for LGA infants despite good maternal glucose control during pregnancy.